2002
DOI: 10.1080/01690960143000290
|View full text |Cite
|
Sign up to set email alerts
|

Activating meaning in time: The role of imageability and form-class

Abstract: A number of studies have shown that the meanings of spoken words are activated early in processing, well before all of the word has been heard. However, these studies have not explicitly taken into account a number of variables which are known to affect word recognition processes. Two important variables are a word's imageability and its form-class. In the experiments reported here we use a cross-modal priming task to investigate the role that these variables play on the time-course with which word meanings ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 74 publications
3
29
1
Order By: Relevance
“…Using their crossmodal paradigm discussed previously, Moss et al (1997, Experiment 2) found a marginal 10 msec of priming ( p 5 .09) for backward associates, which clearly would not have differed from some of their "pure-semantic" effects of 9, 11, and 13 msec reported in their first two studies. Tyler et al (2002) also found a marginally significant correlation (r 5 .212, p 5 .06) between priming effects and backward associative strength in their experiment.…”
Section: Auditory Priming Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Using their crossmodal paradigm discussed previously, Moss et al (1997, Experiment 2) found a marginal 10 msec of priming ( p 5 .09) for backward associates, which clearly would not have differed from some of their "pure-semantic" effects of 9, 11, and 13 msec reported in their first two studies. Tyler et al (2002) also found a marginally significant correlation (r 5 .212, p 5 .06) between priming effects and backward associative strength in their experiment.…”
Section: Auditory Priming Studiesmentioning
confidence: 91%
“…These studies are shown in Table 8, divided according to the presentation modality of the target (visual or auditory) and the type of task used (standard or continuous LDT). Zwitserlood and Schriefers (1995), Moss, McCormick, and Tyler (1997), and Tyler, Moss, Galpin, and Voice (2002) have all examined semantic priming without association using auditory primes and visual targets. Using semantically related Dutch pairs that supposedly do not share an association, Zwitserlood and Schriefers presented participants with auditory vocal onsets (e.g., "cap") compatible with approximately 4 words (e.g., captain, capital, captive, capsize).…”
Section: Auditory Priming Studiesmentioning
confidence: 99%
“…The ascending slope of the N400m response (ϳ200 -450 ms) lies in the time window when lexical-semantic information of written and spoken words is likely to be accessed (Lau et al, 2008). However, as behavioral data indicate that both written and spoken words can be recognized within ϳ500 ms or less (for review, see Tyler et al, 2002;Balota et al, 2004), the effects of both meaning and sound form from 450 ms onwards are likely to reflect postlexical integration of all available information in the context created by the preceding words that may well occur similarly for written and spoken words.…”
Section: Discussionmentioning
confidence: 99%
“…Some words have more semantic associates than do others and therefore differ in their semantic richness (Nelson, McEnvoy, & Schreiber, 1998). A second semantic variable, more frequently examined in the domain of disordered reading than in normal word recognition is concreteness, or the potential to imagine the meaning of a word (Bleasdale, 1987;Collins & Coney, 1998;de Groot, 1989;James, 1975;Kroll & Merves, 1986;Schwanenflugel, Akin, & Luh, 1992;Strain, Patterson, & Seidenberg, 1995;2002;Tyler, Moss, Galpin, & Voice, 2002). Finally, there is the similarity that tends to arise when two words are formed from the same base morpheme so that they are morphologically related (for reviews on Spanish, German and English data see Domínguez, Cuetos, & Segui, 2000;Dohmes, Zwitserlood, & Boelte, 2004;Baayen, Feldman, & Schreuder (submitted); and Feldman, 2000, respectively).…”
Section:  Introductionmentioning
confidence: 99%